A study on printed multiple solid line by combining microcontact and flexographic printing process for microelectronic and biomedical applications - Maksud, M. I. (Pejabat Penerbit, 2013)
Micro-contact printing (μCP) is an outstanding surface patterning technique in micron scale and, also in nano scale. Surface science communities such as engineers and biologists have been promoting attention in μCP and, therefore enriching in improvement to the μCP process itself. However the process is relatively slow in production. In contrast, flexographic technique is a high speed roll to roll process, but low in resolution and still has limitation in printing of micro-scale size. Now a day, low cost fabrication is keys to the successful introduction of printed electronics and roll to roll manufacturing processes. Therefore, study to extend flexographic into the micro-scale size resolutions, may provide an economical commercialization path for electronic devices, given the fact that flexographic is a high speed technique commonly used for printing onto very large area flexible substrates. Although low resolution and poor registration are characteristics of today's flexographic process, it has many potential to realize fine solid line micro size by combining it to micro-contact printing because both of them having similarities in method of carrying printed pattern to a substrates. This work have demonstrated that a 10μm line with 10μm gap was successfully printed by these two combinations of printing techniques, using graphic ink and biological ink which is Fetal Bovine Serum.